Surfacing electrode for crack repair

By using specific ingredients of powdered skin and H08A steel wire in the surfacing welding rod, combined with carbide and mesoporous silica loading technology, the problems of low hardness and poor wear resistance of the surfacing welding layer are solved, and high hardness and resistance are achieved The abrasive welding layer reduces energy consumption and environmental pollution and extends the service life of the sintered trolley.

CN119216872AActive Publication Date: 2024-12-31TANGSHAN LANYAN WELDING MATERIALS TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411646818.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2024-12-31
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

During the repair of sintered trolleys, the hardness and poor wear resistance of welding rods are low, which leads to the repaired parts being easily worn, affecting the normal operation of the equipment. The traditional welding process consumes a lot of energy and is complex.

Method used

Using a coating containing components such as white clay, fluorite, quartz, rutile, titanium iron, high-carbon iron manganese, cerium oxide, metal nickel and carbide, combined with H08A steel wire as the welding core, the metal nickel and carbide are defined by the Mass ratio, enhance hardness and wear resistance, and load tungsten carbide through mesoporous silica to improve the dispersion and stability of the hard phase.

Benefits of technology

It significantly improves the hardness and wear resistance of the surfacing layer, reduces energy consumption, avoids preheating and heat treatment, extends the service life of the sintered trolley, and reduces environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of welding materials, and provides a surfacing welding rod for crack repair, the surfacing welding rod comprises a core wire and a coating wrapping the core wire, the coating comprises the following raw materials in percentage by weight: 1-2% of white clay, 20-30% of fluorite, 1-3% of quartz, 2-4% of rutile, 4-7% of ferrotitanium, 1-3% of high-carbon ferromanganese, 1-3% of ferrosilicon, 4-7% of cerium oxide, 15-17% of metallic nickel, 4-10% of hard phase and the balance of marble, and the core wire is an H08A steel welding wire; and the hard phase is carbide. According to the technical scheme, the problems of low hardness and poor wear resistance of a surfacing welding layer in the related technology are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of welding materials, and in particular to a surfacing welding rod for crack repair. Background Art

[0002] Surfacing welding rod is a welding material used for surfacing welding on the surface of workpieces. It is composed of a layer of coating on the metal core. The coating contains various alloy elements, slag forming agents, arc stabilizers and other ingredients. During the welding process, the coating will melt to form slag to protect the welding pool. At the same time, the alloy elements will transition to the molten pool and fuse with the parent material to form a surfacing layer with special properties on the surface of the parent material. Surfacing welding rods are widely used in machinery manufacturing, metallurgy, electric power and other fields.

[0003] The functions of cladding electrodes mainly include repairing damaged surfaces, enhancing performance, avoiding workpiece scrapping, simplifying repair processes, etc. Among them, for workpieces with damage such as cracks, especially equipment like sintering trolleys that work in an alternating environment of high temperature and cooling and have cracks and cracks, cladding electrodes can be used to fill and repair damaged parts.

[0004] Sintering trolleys are essential key equipment for coke plants and sintering pellet plants in my country and around the world. Ductile iron is usually used in their manufacture. Ductile iron is similar to cast steel to a certain extent. Using it can reduce costs and achieve better results. However, sintering trolleys face many problems during operation. The nature of its work determines that it is in a state of alternating high temperature and cooling for a long time. This long-term transition between hot and cold will cause the ductile iron to become white, change the elongation and plasticity of the material, and then cause cracks in the bearing seat of the trolley. With the long-term use of the bearing seat support of the sintering trolley, the cracks continue to expand, which may eventually lead to the scrapping of the sintering trolley worth millions. In addition, due to the large temperature difference between the natural temperature and the temperature during sintering, cracking problems are also likely to occur.

[0005] Sintering trolleys are the main tools of each factory. Once damaged and when spare parts are not available, it will directly cause production suspension or turnover difficulties. However, with traditional cladding electrodes, even if the trolley is preheated (about 400℃) before welding and heat treated after welding, the cracking phenomenon of the heat affected zone is still relatively serious. At the same time, preheating before welding and heat treatment after welding not only waste a lot of energy and make the welding process complicated, but also increase the labor intensity, causing great economic losses to the enterprise.

[0006] During the sintering process, the sintering trolley needs to carry and transport a large amount of ore, coke and other materials. These materials move on the trolley and will produce continuous friction with the surface of the trolley. If the repaired area with the cladding electrode does not have wear resistance, the repaired area will be easily worn during the long-term material transportation process, thereby affecting the normal operation of the sintering trolley. The high-hardness cladding layer can ensure that the repaired area will not fail again due to wear, deformation or cracking for a long time.

[0007] Therefore, a surfacing welding rod for crack repair is developed to improve the hardness and wear resistance of the surfacing welding layer, and the crack resistance of the welding layer. It is applied to the surfacing welding repair of cast iron trolleys, which not only reduces energy consumption and avoids environmental pollution during the manufacturing process, but also can restore the original shape and size of the scrapped cast iron trolleys through preheating-free and heat-treatment-free surfacing welding, and improve their service life. It has important engineering significance to solve the problem of trolley damage that cannot be repaired, which is common in coke plants and sintering ball plants in my country, and its market space is very broad. Summary of the invention

[0008] The invention provides a surfacing welding rod for crack repair, which solves the problems of low hardness and poor wear resistance of the surfacing welding layer in the related art.

[0009] The technical solution of the present invention is as follows: The present invention provides a surfacing welding rod for crack repair, comprising a welding core and a coating coated outside the welding core, the coating comprising the following raw materials in weight percentage: 1% to 2% of white clay, 20% to 30% of fluorite, 1% to 3% of quartz, 2% to 4% of rutile, 4% to 7% of ferrotitanium, 1% to 3% of high carbon ferromanganese, 1% to 3% of ferrosilicon, 4% to 7% of cerium oxide, 15% to 17% of metallic nickel, 4% to 10% of hard phase, and the balance is marble, the welding core is H08A steel welding wire; The hard phase is carbide.

[0010] As a further technical solution, the carbide includes one or more of tungsten carbide, boron carbide, and titanium carbide.

[0011] As a further technical solution, the mass ratio of the metallic nickel to the hard phase is 3:1-2.

[0012] In the present invention, the mass ratio of metal nickel to carbide is limited to enhance the strengthening effect between the two, thereby improving the hardness and wear resistance of the cladding layer.

[0013] As a further technical solution, when the carbide consists of tungsten carbide and titanium carbide, the mass ratio of the tungsten carbide to the titanium carbide is 2~3:1.

[0014] In the present invention, tungsten carbide and titanium carbide are added as carbides at the same time, and their mass ratio is limited to exert their synergistic effect, form a more reasonable hard phase distribution, enhance the bonding strength between the two and metal nickel, and further improve the hardness and wear resistance of the cladding layer.

[0015] As a further technical solution, the tungsten carbide is loaded tungsten carbide, the carrier of the loaded tungsten carbide is mesoporous silica, and the active ingredient is tungsten carbide.

[0016] In the present invention, mesoporous silica is used as a carrier to load tungsten carbide, thereby improving the dispersibility of tungsten carbide, enhancing the stability of tungsten carbide, and further improving the hardness and wear resistance of the cladding layer.

[0017] As a further technical solution, in the raw material for loading tungsten carbide, the mass ratio of the carrier to the active ingredient is 10:1-2.

[0018] As a further technical solution, the preparation method of the loaded tungsten carbide includes the following steps: dispersing the precursor of tungsten carbide in a solvent, adding mesoporous silica, drying after uniform dispersion, and obtaining the loaded tungsten carbide through a carbonization reaction.

[0019] As a further technical solution, the diameter of the mesoporous silica is 100-400 nm.

[0020] As a further technical solution, the precursor of the tungsten carbide includes tungsten oxide and graphite, and the molar ratio of the tungsten oxide to the graphite is 1:1.

[0021] As a further technical solution, the temperature of the carbonization reaction is 1200-1300° C., and the insulation time is 2-4 hours.

[0022] As a further technical solution, the ferrosilicon is purified ferrosilicon, the purification temperature is 720-750° C., and the insulation time is 0.8-1.2 h.

[0023] As a further technical solution, the high carbon ferromanganese is purified high carbon ferromanganese, the purification temperature is 300-350°C, and the insulation time is 0.8-1.2h.

[0024] The present invention also provides a method for preparing a cladding electrode for crack repair, comprising the following steps: weighing the raw materials of the coating weight percentage, mixing them evenly, applying a binder on the welding core, drying and polishing, and then obtaining the cladding electrode for crack repair.

[0025] As a further technical solution, the drying temperature is 250-300°C.

[0026] As a further technical solution, the binder includes one or both of water glass and clay.

[0027] As a further technical solution, the iron content of the ferrotitanium is 30wt%~80wt%, the carbon content of the high carbon ferromanganese is 6wt%~7wt%; and the silicon content of the ferrosilicon is 70wt%~75wt%.

[0028] The working principle and beneficial effects of the present invention are: In the present invention, mineral materials such as marble, fluorite, quartz and alloy materials such as ferrotitanium and high carbon ferromanganese are used as the main materials, and auxiliary materials such as metal nickel and cerium oxide are added. On this basis, carbides are added as hard phases to prepare a welding rod coating layer. Carbides improve the hardness of the surfacing layer by hindering dislocation movement, and improve the wear resistance of the surfacing layer by resisting abrasive wear. DETAILED DESCRIPTION

[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] In the following examples and comparative examples: Marble: particle size is 400 mesh; White clay: particle size is 400 mesh; Quartz: particle size is 325 mesh; Rutile: average particle size is 0.3 μm; Ferro-titanium: iron content is 40wt%; High carbon ferromanganese: carbon content is 7wt%; Ferrosilicon: Silicon content 75wt%; Cerium oxide: average particle size is 1.5 μm; Metal nickel: purity is 99.99%; Mesoporous silica: 300nm in diameter; Tungsten oxide: average particle size 40nm; Graphite: average particle size 10nm; Water glass: potassium water glass, effective content is 40wt%, modulus is 2.6~2.8m; Chromium boride: average particle size is 1 μm; Coating: thickness 1mm; Welding core: H08A steel welding wire, diameter 2mm.

[0031] Example 1 A surfacing welding rod for crack repair includes a welding core and a coating covering the welding core, wherein the coating includes the following raw materials in percentage by weight: 1% white clay, 20% fluorite, 1% quartz, 2% rutile, 4% ferro-titanium, 1% high carbon ferro-manganese, 1% ferrosilicon, 4% cerium oxide, 15% metallic nickel, 4% hard phase, and the balance is marble, of which the hard phase is tungsten carbide; The welding core is H08A steel welding wire; Ferrosilicon is purified at 720°C with a holding time of 1.2 h, and high carbon ferromanganese is purified at 300°C with a holding time of 1.2 h. The raw materials for the coating are prepared according to the above weight percentages, mixed evenly using a roller, then water glass is added and stirred evenly, welding rods are extruded using a welding rod coater, dried at 250°C, and then ground to obtain welding rods for crack repair.

[0032] Example 2 A surfacing welding rod for crack repair includes a welding core and a coating covering the welding core, wherein the coating includes the following raw materials in percentage by weight: White clay 1.5%, fluorite 22.7%, quartz 1.7%, rutile 3.8%, ferrotitanium 5.8%, high carbon ferromanganese 2.5%, ferrosilicon 1.6%, cerium oxide 5.3%, metallic nickel 16%, hard phase 5%, the balance is marble, of which the hard phase is tungsten carbide; The welding core is H08A steel welding wire; Purify ferrosilicon at 730°C and keep it warm for 1 hour. Purify high carbon ferromanganese at 320°C and keep it warm for 1 hour. Prepare the raw materials of the coating according to the above weight percentage, mix them evenly with a roller, add water glass and stir evenly, extrude the welding rod with a welding rod coater, dry the welding rod at 280°C, and then grind the head and tail to obtain the surfacing welding rod for crack repair.

[0033] Example 3 A surfacing welding rod for crack repair includes a welding core and a coating covering the welding core, wherein the coating includes the following raw materials in percentage by weight: 2% white clay, 30% fluorite, 3% quartz, 4% rutile, 7% ferro-titanium, 3% high carbon ferro-manganese, 3% ferrosilicon, 7% cerium oxide, 17% metallic nickel, 5% hard phase, and the balance is marble, of which the hard phase is tungsten carbide; The welding core is H08A steel welding wire; Ferrosilicon is purified at 750°C with a holding time of 0.8h, and high carbon ferromanganese is purified at 350°C with a holding time of 0.8h. The raw materials for the coating are prepared according to the above weight percentages, mixed evenly with a roller, then water glass is added and stirred evenly, and the welding rod is extruded with a welding rod coater, dried at 300°C, and then ground to obtain a surfacing welding rod for crack repair.

[0034] Example 4 Compared with Example 1, Example 4 is different in that tungsten carbide is replaced by an equal amount of titanium carbide.

[0035] Example 5 Compared with Example 1, the difference in Example 5 is that the addition amount of the hard phase is 5%.

[0036] Example 6 Compared with Example 1, the difference in Example 6 is that the addition amount of the hard phase is 10%.

[0037] Example 7 Compared with Example 6, the difference of Example 7 is that the hard phase is composed of tungsten carbide and titanium carbide in a mass ratio of 2:1.

[0038] Example 8 Compared with Example 6, the difference of Example 8 is that the hard phase is composed of tungsten carbide and titanium carbide in a mass ratio of 3:1.

[0039] Example 9 The preparation method of loaded tungsten carbide includes the following steps: dispersing 1 part of a precursor in 100 parts of ethanol, adding 10 parts of mesoporous silica, ultrasonicating for 1 hour and then drying, and carbonizing at a temperature of 1200°C for 3 hours to obtain loaded tungsten carbide, wherein the precursor is composed of tungsten oxide and graphite in a molar ratio of 1:1.

[0040] Compared with Example 8, the difference of Example 9 is that tungsten carbide is replaced by an equal amount of supported tungsten carbide obtained by the above preparation method.

[0041] Example 10 Compared with Example 9, the difference in Example 10 is that the amount of the precursor added is 2 parts.

[0042] Comparative Example 1 Compared with Example 1, Comparative Example 1 is different in that no hard phase is added.

[0043] Comparative Example 2 Compared with Example 1, Comparative Example 2 is different in that tungsten carbide is replaced by an equal amount of chromium boride.

[0044] The sintering trolley was repaired using the surfacing welding rods for crack repair prepared in Examples 1 to 10 and Comparative Examples 1 to 2. The welding rods were dried at 300°C for 1 hour before welding to remove the crystal water in the coating. A DC welding machine was used for reverse connection. The welding current was 180A and the welding voltage was 80V. The trolley part was not preheated before welding and heat treatment was not performed after welding. The repaired sintering trolley was tested according to the following method: 1. Brinell hardness: Test the Brinell hardness of the sample according to the single-point determination test method specified in GB / T 2654-2008 "Test method for hardness of welded joints".

[0045] 2. Wear weight loss: The weld layer obtained by surfacing welding is made into a φ32×10mm cylinder and tested on an MMW-1A vertical universal friction and wear testing machine. The wear time is 10 minutes. The difference in mass before and after wear is the wear weight loss.

[0046] The test results are shown in the following table: Table 1 Application performance test results of the surfacing welding rods for crack repair prepared in Examples 1 to 10 and Comparative Examples 1 to 2

[0047] Compared with Comparative Examples 1 and 2, Example 1 adds tungsten carbide as a hard phase. As a result, the Brinell hardness of Example 1 is better than that of Comparative Examples 1 and 2, and the weight loss due to wear is less than that of Comparative Examples 1 and 2, indicating that the addition of a hard phase and the hard phase being carbide can improve the hardness and wear resistance of the surfacing layer.

[0048] Compared with Examples 1 and 4, Examples 7 and 8 simultaneously add tungsten carbide and titanium carbide as hard phases. As a result, the Brinell hardness of Examples 7 and 8 is better than that of Examples 1 and 4, and the weight loss due to wear is less than that of Examples 1 and 4, indicating that tungsten carbide and titanium carbide play a synergistic role and can improve the hardness and wear resistance of the cladding layer.

[0049] Compared with Example 8, Examples 9 and 10 added loaded tungsten carbide. As a result, the Brinell hardness of Examples 9 and 10 was better than that of Example 8, and the weight loss due to wear was less than that of Example 8, indicating that after tungsten carbide was loaded with mesoporous silica, the hardness and wear resistance of the obtained cladding layer were better.

[0050] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A surfacing electrode for crack repair, characterized in that: The invention comprises a welding core and a coating coated on the welding core, wherein the coating comprises the following raw materials in weight percentage: 1%-2% kaolin, 20%-30% fluorite, 1%-3% quartz, 2%-4% rutile, 4%-7% ferrotitanium, 1%-3% high carbon ferromanganese, 1%-3% ferrosilicon, 4%-7% cerium oxide, 15%-17% metallic nickel, 4%-10% hard phase, and the balance is marble. The welding core is H08A steel welding wire; the hard phase is carbide.

2. A surfacing welding rod for crack repair according to claim 1, characterized in that: The carbide includes one or more of tungsten carbide, boron carbide and titanium carbide.

3. A surfacing welding rod for crack repair according to claim 1, characterized in that: The mass ratio of the metallic nickel to the hard phase is 3:1-2.

4. A surfacing welding rod for crack repair according to claim 2, characterized in that: When the carbide consists of tungsten carbide and titanium carbide, the mass ratio of the tungsten carbide to the titanium carbide is 2-3:

1.

5. A surfacing welding rod for crack repair according to claim 4, characterized in that: The tungsten carbide is loaded tungsten carbide, the carrier of the loaded tungsten carbide is mesoporous silica, and the active component is tungsten carbide.

6. A surfacing welding rod for crack repair according to claim 5, characterized in that: In the raw material for loading tungsten carbide, the mass ratio of the carrier to the active ingredient is 10:1-2.

7. The surfacing welding rod for crack repair according to claim 5, characterized in that: The preparation method of the loaded tungsten carbide comprises the following steps: dispersing the precursor of tungsten carbide in a solvent, adding mesoporous silica, drying after uniform dispersion, and obtaining the loaded tungsten carbide through a carbonization reaction.

8. The surfacing welding rod for crack repair according to claim 7, characterized in that: The diameter of the mesoporous silica is 100-400 nm.

9. The surfacing welding rod for crack repair according to claim 7, characterized in that: The precursor of the tungsten carbide includes tungsten oxide and graphite, and the molar ratio of the tungsten oxide to the graphite is 1:

1.

10. The surfacing welding rod for crack repair according to claim 7, characterized in that: The temperature of the carbonization reaction is 1200-1300° C., and the insulation time is 2-4 hours.

Citation Information

Patent Citations

  • Special welding electrode for surfacing and repairing broken teeth of cast iron gear

    CN101920404A

  • Special welding electrode for surfacing and repairing broken teeth of cast steel gear

    CN101920414A

  • Special welding rod used for surfacing reparation of high carbon steel type high-speed railway base tamping pick

    CN102528321A

  • Special electrode for overlaying and repairing high-chromium cast iron type high-speed rail substructure tamping pick

    CN102554502A

  • High-hardness wear-resistant overlaying welding electrode and preparation method thereof

    CN111922549A

Cited By

  • Welding rod for repairing surfacing welding of nodular cast iron sintering pallet

    CN119897631A